Morality for beautiful girls [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2003)
"The No 1 Ladies' Detective Agency" introduced the engaging and sassy owner of Botswana's only detective agency, Precious Ramotswe. This latest novel finds her expanding her business to take in the world of car repair and a beauty pageant.